Institutional Fragmentation and Collaborative Governance in Urban Governance: A Delphi-Informed Case Study from Kendari, Indonesia - Haeruddin Haeruddin; Roni Ekha Putera; Aqil Teguh Fathani; Tengku Rika Valentina (Journal Public Policy, 2026)
Growing secondary cities often face fragmented authority, dispersed policy information and weak cross-sector follow-up, which constrain integrated urban governance. This study examines how institutional fragmentation shapes urban governance in Kendari City, Indonesia; and identifies feasible strategies for institutional integration through collaborative governance. A two-stage qualitative case study was employed. The first stage combined document review, field observation and interviews with 45 informants from government, legislative bodies, implementers, academics, civil society, business actors and community leaders to map the forms and consequences of fragmentation. The second stage used a two-round Delphi exercise with 10 experts to validate qualitative themes and prioritize integration strategies. The findings show that fragmentation operates through four interrelated layers: structural, procedural, informational and relational fragmentation. Expert consensus indicates that integration should prioritize clearer cross-sector coordinating authority, collaborative forums with binding follow-up, integrated data and shared indicators and facilitative leadership. The study contributes to urban governance scholarship by treating fragmentation as a multi-layer institutional condition rather than an administrative weakness. It further advances collaborative governance scholarship by conceptualizing institutionalized collaboration as a mechanism linking role clarity, shared information, binding follow-up and joint accountability. These findings imply that growing cities require collaboration embedded in institutional design, not limited to routine coordination.